Stages of Adoption of “Treatment as Prevention” Among HIV-Negative Men Who Have Sex with Men Who Engage in Exchange Sex - Meunier, Étienne (AIDS Patient Care STDS, 2020)
Prior research found low acceptability of HIV treatment as prevention (TasP; or Undetectable = Untransmittable) among HIV-negative men who have sex with men (MSM). This study reports on qualitative data regarding TasP adoption in a sample of 170 self-reported HIV-negative MSM who had engaged in exchange sex (received money, drugs, or other things in exchange for sex). We classified participants along five stages of TasP adoption: 1–unaware of TasP (11.2%); 2–aware, but perceived ineffective (17.1%); 3–perceived effective, but unwilling to use (35.3%); 4–willing to rely on TasP, but had never done so (24.1%); and 5–had relied on TasP (12.4%). Obstacles to TasP adoption included the following: not believing that it could completely prevent HIV transmission; deeply ingrained fears of HIV/AIDS; concerns about viral load fluctuation; and reluctance to trust a partner's claimed undetectable status. TasP promotion efforts, which can decrease barriers to HIV testing and HIV stigma, will be more effective if tailored to the obstacles specific to each stage of TasP adoption.